ANALISIS INTERAKSI MASYARAKAT PERKOTAAN DAN MASYARAKAT PEDESAAN KOTA PALU, KABUPATEN DONGGALA DAN KABUPATEN SIGI - Aqshah, Mohammad (Katalogis, 2013)
The purpose this: 1) to know the interaction among that happen in palu city, Donggala regency, and the society of Sigi regerency; and 2) to know the factor that cause a happen the interaction among Palu city, Donggala society and Sigi regency society. The population this research are 440.125 people in research area by using Sloving Formula with crisis value is 10%Â i. Interaction is bigger happen between gunung Bale Area Palu City . The higher interaction in the both area because thatâ€™s trade area, and the measure lie is near relative with status way is higher than other area, the population indicate is more than other if compare with other area; 2) to fulfill the needs the staplefood,facility, and basic service, preparing the raw materials, human resource for indusrty, trade and economic activity become encourage factors cause make economic interaction among Palu city society, Donggala regency society and Sigi regency Society.